STUDI KESADARAN PAJAK TERHADAP KEPATUHAN PAJAK DAN RELIGIUSITAS SEBAGAI PEMODERASI - Sukmana, Sela; Djadang, Syahril; JMV, Mulyadi (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2018)
This study aims to examine the effect of tax education, tax knowledge, and tax audit on tax compliance, with religiosity as a moderator in the Office of Tax Service Pratama Jakarta Tanah Abang Tiga. The data used in this study is the primary data obtained through a questionnaire of 400 respondents Taxpayers registered in KPP Pratama Jakarta Tanah Abang Tiga. The results of this study indicate that tax education, tax knowledge, and tax audit significantly influence tax compliance, while religiosity has no significant effect on tax compliance, but the interaction between religiosity and tax education and interaction of religiosity and tax knowledge have a significant effect on tax compliance.